2008
DOI: 10.1111/j.1532-5415.2007.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Counseling and Support Reduce Burden and Depressive Symptoms in Caregivers of People with Alzheimer's Disease During the Transition to Institutionalization? Results from the New York University Caregiver Intervention Study

Abstract: OBJECTIVES-To determine whether counseling and support reduces the burden and depressive symptoms of spouse caregivers of Alzheimer's patients during the institutionalization transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
131
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 41 publications
3
131
1
2
Order By: Relevance
“…This research finding also supported from previous study which mentioned that counseling and getting involved at supporting group may reduce caregivers' burden and depressive syndrom 10 . Supporting group is significantly deliver positive effect to caregiver's psychological health, depression, burden and social relationship 11 .In line with other research which explained that caregiver burden getting decline on intervention group, seen as previous mean was 42 become 35.44, after undergoing education program on 1 month, while on control group was increased, and found significant difference between intervention and control group 12 .…”
Section: IVsupporting
confidence: 80%
“…This research finding also supported from previous study which mentioned that counseling and getting involved at supporting group may reduce caregivers' burden and depressive syndrom 10 . Supporting group is significantly deliver positive effect to caregiver's psychological health, depression, burden and social relationship 11 .In line with other research which explained that caregiver burden getting decline on intervention group, seen as previous mean was 42 become 35.44, after undergoing education program on 1 month, while on control group was increased, and found significant difference between intervention and control group 12 .…”
Section: IVsupporting
confidence: 80%
“…Even though the effectiveness of psychotropic drugs is limited and some (for instance, typical antipsychotics) have potentially harmful side effects, psychotropic drugs are widely used in nursing homes to treat MPS in psychogeriatric patients [2,5,15,16]. Integrative psychotherapeutic programmes are still lacking, even though previous studies have indicated that psychotherapeutic treatment may be effective at reducing individual psychiatric symptoms (such as depression and anxiety) and caregiver burden in both nursing home and primary care settings [17,18,19,20,21,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Alternative care possibilities, such as visiting caregivers or dedicated inpatient institutions, are not available in Turkey. Worldwide, approximately 8.9 million persons are estimated to be looking after patients over 50 affected by Alzheimer's or dementia from other causes [4] . Caregivers who lack the training needed care for these patients are under pressure because of the increasing needs.…”
Section: Introductionmentioning
confidence: 99%